A novel linear elastic actuator for minimally invasive surgery: development of a surgical gripper. (23rd September 2016) - Gerboni, G; Brancadoro, M; Tortora, G; Diodato, A; Cianchetti, M; Menciassi, A
Abstract: Minimally invasive surgery (MIS) applications require lightweight actuators that can generate a high force in a limited volume. Among pressure driven actuators, fluid elastic actuators demonstrate high potential for use in the medical field. They are characterized by nearly no friction and wear and they can be made of low-cost biocompatible elastomers. However, when compared to traditional piston-cylinder fluid actuators, fluid elastic actuators often result in smaller output forces as well as weaker return forces. This work is about the design of a linear elastic actuator (LEA) which is able to develop relevant pulling-pushing force in one direction. The LEA is composed of entirely disposable materials and it requires a simple manufacturing process. Thanks to its design, the LEA can be compared to traditional piston-cylinders actuators in terms of output forces (up to 7 N) with the advantage of using relative low working pressures (0, 2 MPa). The actuator has been used for the actuation of a gripper for MIS, as a case study. The whole range of gripping forces developed by the tool actated by the LEA has been evaluated, thus verifying that the gripping device, is able to meet the force requirements for accomplishing typical surgical tasks.